Measures of the Output Gap in the Euro-Zone: An Empirical Assessment of Selected Methods - Jörg Döpke; Odile Chagny (Kiel Institute of World Economics (IfW), 2001)
The paper discusses some widely used methods for estimating output gaps based on aggregated data for the eurozone. Though these methods exhibit some common features, an empirical comparison demonstrates that the various techniques differ substantially. In particular, the correlation of output gaps calculated with different methods is generally low, the methods imply different turning points, and the estimated level of the output gap differs greatly. Moreover, tests suggest that some of the methods commonly used have only limited information content for inflation forecasting in the euro-zone. Conclusions for business cycle analysis and economic policy are offered. – – Der Aufsatz untersucht einige populäre Methoden zur Messung des Output Gaps auf der Basis von aggregierten Daten für die Euro-Zone. Obwohl die Methoden einige wichtige gemeinsame Eigenschaften aufweisen, zeigen sie auch erhebliche Unterschiede; insbesondere ist die Korrelation zwischen Output-Gap-Schätzungen auf Basis verschiedener Methoden niedrig, die Ansätze implizieren differierende Wendepunkte und das Niveau des Output Gaps variiert stark. Empirische Untersuchungen zeigen zudem, dass der Informationsgehalt der Gap-Variablen für die Prognose der Inflationsrate nur sehr klein ist. Einige Schlussfolgerungen hinsichtlich der Nützlichkeit von Output-Gap-Schätzungen und für die Wirtschaftspolitik werden gezogen.
Keywords: E32; 330; Output Gap; European Monetary Union; Business Cycles; Wirtschaftspotential; Konjunkturforschung; Schätztheorie; Ökonometrisches Modell; Theorie; Wirtschaftspotential; Konjunktur; Europäische Wirtschafts- und Währungsunion; Schätzung; EU-Staaten